النّزعة الأسلوبية عند عبد السلام المسدي وتمثلاتها في النقد العربي: دراسة في كتاب " النقد والحداثة - بن قويدر, عالم; مختار, زوليخة (جامعة الوادي - University of Eloued, 2022)
حظيت المناهج النّقدية والأسلوبية منها خاصة بعناية الدّارسين؛ إذ يتصدرهم الناقد التونسي "عبد السلام المسدي" الذي تميزت أسلوبيته بالمرونة، وقد لمسنا ذلك من خلال مدوناته وكذا النقاد الذين نهلوا منها تنظيرا وتطبيقا. لذا ارتأينا في هذه الورقة البحثية رصد المرجعية الأسلوبية للناقد وأثرها في الدرس النقدي العربي، وقد دفعنا هذا إلى طرح عدد من التساؤلات: ما سمات الأسلوبية عند الناقد عبد السلام المسدي؟ وكيف جمع فيها بين الأصالة العربية والحداثة الغربية؟ وكيف استثمر النقد العربي جهوده في قراءة الأدب وتحليل الخطابات؟ ومن خلال المنهج الوصفي والتحليلي والنظر في جهوده النقدية، توصلنا إلى أنّ قراءاته تميّزت بالتجديد من خلال الجمع بين التأصيل التراثي العربي والنهل من الثقافة الغربية. وذلك للوصول إلى أسس منهجية أسلوبية كفيلة بسد الثغرات النقدية في النقد العربي. Abstract: Critical curricula, such as stylistics, have received a big scholors' attention; Led by tunisian critic Abdelsalam El Massadi, whose style has been characterized by flexibility. We saw this through his works, as well as the critics who benefited from them in theory and practice. So we decided in this paper to monitor the stylistic reference of the critic Al-Massadi and its impact on the Arab critical discipline. Thus, we will ask some questions: What are the stylistic characteristics of the critic Abdul Salam Al-Massadi? How did he combine Arab originality with Western modernity? How did Arab criticism invest the efforts of this critic in reading literature and analyzing discourses? Through the descriptive and analytical approach and consideration of his critical efforts, we concluded that his readings were characterized by renovation by combining Arab heritage rooting with Western culture in order to reach the foundations of a stylistic methodology that can bridge the critical gaps in Arab criticism.
The Stylistic Tendency Of Abd Al-salam Al-masadi And Its Representations In Arab Criticism: A Study In The Book "critique And Modernity"
مقال
Keywords: أسلوبية، نقد، تراث، حداثة، تحليل الخطاب; stylistics; criticism; heritage; modernity; Discourse analysi